Back to Course

JSS3: MATHEMATICS - 1ST TERM

0% Complete
0/0 Steps
  1. Binary Number System I | Week 1
    5Topics
    |
    1 Quiz
  2. Binary Number System II | Week 2
    6Topics
    |
    1 Quiz
  3. Word Problems I | Week 3
    4Topics
    |
    1 Quiz
  4. Word Problems with Fractions II | Week 4
    1Topic
    |
    1 Quiz
  5. Factorisation I | Week 5
    4Topics
    |
    1 Quiz
  6. Factorisation II | Week 6
    3Topics
    |
    1 Quiz
  7. Factorisation III | Week 7
    3Topics
    |
    1 Quiz
  8. Substitution & Change of Subject of Formulae | Week 8
    2Topics
    |
    1 Quiz
  9. Simple Equations Involving Fractions | Week 9
    3Topics
    |
    1 Quiz
  10. Word Problems | Week 10
    1Topic
    |
    1 Quiz
Lesson 3, Topic 2
In Progress

Product

Lesson Progress
0% Complete

This is the result obtained when two numbers are multiplied together.

N.B. When multiplying decimals, remove the decimal point before you multiply and replace it after multiplying.

Example 1

a. 8 and 6.5

Screen Shot 2021 09 15 at 6.35.14 PM

b. 9.2 and -4.6

1d.p  x 1d.p = 2d.ps

Screen Shot 2021 09 15 at 6.45.05 PM

c. Find the product of \( \scriptsize – 3 \frac{1}{9} \; and \; – 4 \frac{2}{7} \)

First, convert to improper fractions.

\( -\frac{28}{9} \; \times \; -\frac{30}{7} = +\frac {40}{3} \\ = \scriptsize 13 \frac{1}{3} \; or \; 13.33 \)

Note:   \( \scriptsize – \; \times \; – \; = + \)

d. The product of a positive number and itself is \( \;\scriptsize 3 \frac{1}{16}\) What is the number

Solution

Let the number be x

\( \scriptsize x \; \times \; x = 3 \frac{1}{16}\\ \scriptsize x^2 = \normalsize \frac{49}{16} \)

Take the square root of both sides

\( \scriptsize \sqrt{x^2} = \sqrt{\normalsize \frac{49}{16}}\\ \scriptsize x = \normalsize \frac{7}{4} = \scriptsize 1 \frac{3}{4}\)

e. When a number is tripled and five times the number is subtracted, the result is 3.7. What is the number?

Solution

 Let the number be x

 3x  – 5x  = 3.7

-2x  =  3.7

-2x  =  \(\frac{37}{10}\)

Divide both sides by -2

:- \(\frac{-2x}{-2} =\frac{ \frac{37}{10}}{-2}\)

x = \(\frac{37}{10} \; \times \; \frac{1}{-2} \\ = -\frac{37}{20}\scriptsize = -1\frac{17}{20}\)

back-to-top
error: